East European capitalism – What went wrong? - Dorothee Bohle (Intervention. European Journal of Economics and Economic Policies, 2009)
First paragraph: Not all that long ago, the East European newcomers to the European Union (EU) were considered economic miracles which successfully weathered the storms of transformation from socialism, and were ready to settle on stable democratic capitalist development paths. It was even assumed that these countries, toughened by the experience of repeated crises in the 1990s and backed by EU-entry requirements, had developed regulations and institutions that would prove resistant to the current global crisis. Things have turned out otherwise. Almost all new EU member states have accumulated major economic imbalances, and are boarding on steep recessions. Two countries – Hungary and Latvia – had already to turn to the International Monetary Fund (IMF) in order to defend their currencies and keep their economies afloat. Other countries of the region are prone to follow. The crisis in Eastern Europe is not only economic. Surging protests and the increasing appeal of political illiberalism in the region attest to an end of the »political economy of patience« (Offe 1991) which characterized the first years of post-socialist transformation.
Keywords: 330